Hepatitis B virus envelope proteins can serve as therapeutic targets embedded in the host cell plasma membrane. (22nd November 2021) - Zhao, Lili; Chen, Fuwang; Quitt, Oliver; Festag, Marvin; Ringelhan, Marc; Wisskirchen, Karin; Festag, Julia; Yakovleva, Luidmila; Sureau, Camille; Bohne, Felix; Aichler, Michaela; Bruss, Volker; et al.
Abstract: Hepatitis B virus (HBV) infection is a major health threat causing 880, 000 deaths each year. Available therapies control viral replication but do not cure HBV, leaving patients at risk to develop hepatocellular carcinoma. Here, we show that HBV envelope proteins (HBs)—besides their integration into endosomal membranes—become embedded in the plasma membrane where they can be targeted by redirected T‐cells. HBs was detected on the surface of HBV‐infected cells, in livers of mice replicating HBV and in HBV‐induced hepatocellular carcinoma. Staining with HBs‐specific recombinant antibody MoMab recognising a conformational epitope indicated that membrane‐associated HBs remains correctly folded in HBV‐replicating cells in cell culture and in livers of HBV‐transgenic mice in vivo. MoMab coated onto superparamagnetic iron oxide nanoparticles allowed to detect membrane‐associated HBs after HBV infection by electron microscopy in distinct stretches of the hepatocyte plasma membrane. Last but not least, we demonstrate that HBs located on the cell surface allow therapeutic targeting of HBV‐positive cells by T‐cells either engrafted with a chimeric antigen receptor or redirected by bispecific, T‐cell engager antibodies. Take Aways: HBs become translocated to the plasma membrane. Novel, recombinant antibody confirmed proper conformation of HBs on the membrane. HBs provide an interesting target by T‐cell‐based, potentially curative therapies. Abstract : Surface immunoprecipitation of HBS confirmed that membrane‐associated HBs remains correctly folded in HBV‐replicating cells in cell culture. MoMab coated onto superparamagnetic iron oxide nanoparticles allowed to detect membrane‐associated HBs after HBV infection by electron microscopy in distinct stretched of the hepatocyte plasma membrane. Last but not least, we demonstrate that HBs located on the cell surface allow therapeutic targeting of HBV‐positive cells by T‐cells either engrafted with a chimeric antigen receptor or redirected by bispecific, T‐cell engager antibodies.